Impact of Training and Assistance on Home Industry SMEs Development by Housewives in Klambir Lima Village - Widodo, Slamet; Suhendi; Putranto, Muhammad Agung (Yayasan Sinergi Kawula Muda, 2024)
Micro, Small and Medium Enterprises (MSMEs) in the home industry sector managed by housewives have significant potential in supporting the local and national economy. This research aims to identify the impact of training and mentoring on the development of MSMEs in Klambir Lima Village, Deli Serdang Regency, North Sumatra. The research problem raised is whether the training and assistance provided can effectively improve the development of MSMEs managed by housewives. The methodology used is a quantitative approach with a census method on 49 MSME actors in the village. The research results show that training and mentoring do not have a significant impact on the development of MSMEs (t-calculated value for training -1.456 < t-table 1.677; significance 0.152 > 0.05 and t-calculated value for mentoring 0.739 < t-table 1.677; significant 0.464 > 0.05). On the other hand, the marketing aspect has a significant positive impact on the development of MSMEs (t-value 3.134 > t-table 1.677; significance 0.003 < 0.05). Multiple linear regression analysis shows that training, mentoring and marketing simultaneously have a significant impact on the development of MSMEs (F value 3.336 > F-table 2.50; significance 0.028 < 0.05), with marketing as the most crucial factor. In conclusion, an effective marketing strategy is the key to increasing the productivity and development of MSMEs. More focused support on marketing aspects, as well as improving the quality of training and mentoring, is needed to help MSMEs overcome challenges and improve their performance.